‘Dark, mysterious, and undocumented’: the middlebrow fantasy and the fantastic middlebrow - Thomas, S (2013)
The concept of ‘middlebrow’ literature in the twentieth century, which received minimal critical attention from the Leavises onwards, has recently become a site of literary and sociological interest, especially regarding the interwar period. This thesis considers the ways in which a corporate middlebrow identity, amongst an intangible community of like-minded readers, was affected by a popularity of the fantastic in the 1920s and 1930s. This subgenre, which I term the ‘domestic fantastic’ (in which one or more elements of the fantastic intrude into an otherwise normalised domestic world) allowed middlebrow authors and readers to focalise and interrogate anxieties affecting the status of the home and its inhabitants which were otherwise either too taboo or, conversely, too well-worn for a traditional, non-fantastic examination. This fantastic vogue was largely initiated by the success of David Garnett’s metamorphosis novel Lady Into Fox (1922), which prepared the way for the other novels discussed in this thesis, predominantly Sylvia Townsend Warner’s Lolly Willowes (1926), Elinor Wylie’s The Venetian Glass Nephew (1926), Ronald Fraser’s Flower Phantoms (1926), Edith Olivier’s The Love-Child (1927), John Collier’s His Monkey Wife (1930) and Green Thoughts (1932), and Frank Baker’s Miss Hargreaves (1940). Through the lenses of metamorphosis, creation, and witchcraft, these novels respond to and reformulate contemporary debates concerning sexuality in marriage, childlessness, and autonomous space for unmarried women. The ‘middlebrow fantasy’ of the stable, idealised home was being revealed as untenable, and the fantastic responded. During the interwar years, when assessments of British society were being widely recalibrated, the domestic fantastic was a subgenre which produced a select but significant range of novels which (whether playful or poignant, hopeful or tragic, nostalgic or progressive) provided the means for both author and reader to interrogate and comment upon the most pervading middle-class social anxieties, in unusual and revitalising ways.